1997
DOI: 10.1002/(sici)1097-4644(19970701)66:1<43::aid-jcb6>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the function of Rho A protein in cardiac myofibrillogenesis

Abstract: The aim of this study was to provide morphological evidence for the presence of rho A protein in developing cardiomyocytes and to investigate its possible role in myofibrillogenesis. Immunostaining with a monoclonal anti-rho antibody gave a diffuse pattern in the cytosol of cultured cardiomyocytes. Introduction of C3 exoenzyme into the cells by electroporation was used to inactivate rho A protein by ADP-ribosylation. An immunostaining with anti-vinculin, anti-talin, and anti-integrin antibodies showed the foca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Conversely, a constitutively activated mutant of RhoA induced ANF expression and the organization of actin myofilaments into sarcomeric units (11). These data, together with those of other laboratories (12)(13)(14)(15), suggested that RhoA was a mediator of hypertrophic responses in cardiomyocytes.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Conversely, a constitutively activated mutant of RhoA induced ANF expression and the organization of actin myofilaments into sarcomeric units (11). These data, together with those of other laboratories (12)(13)(14)(15), suggested that RhoA was a mediator of hypertrophic responses in cardiomyocytes.…”
Section: Introductionsupporting
confidence: 58%
“…More recently, we and others have demonstrated that a Ras-related small G protein, RhoA, is also a key mediator of hypertrophic responses in ventricular myocytes (10)(11)(12)(13)(14)(15). RhoA belongs to the Rho subfamily of GTPbinding proteins best known for their involvement in the regulation of the actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…The morphological similarity between the BAEC transition from stress fiber to SPAN and actin remodeling in embryonic cardiomyofibrillogenesis suggests possible mechanistic similarity of filament reorganization. Indeed, the RhoA pathway participates in cardiac myofibrillogenesis (5,85).…”
Section: Discussionmentioning
confidence: 99%
“…In the myocardium, the small GTP-binding proteins, Ras, Rho, and Rac, and oxidative stress are involved in the hypertrophic response (136,137). Indeed, recent animal studies suggest that a phagocyte-type NADPH oxidase may be a relevant source of ROSin the myocardium (138)(139)(140).…”
Section: Effects Of Statins On the Myocardiummentioning
confidence: 99%